The family and the school as childhood socialising agencies: an analysis in the light of the sociology of childhood - Lasneaux, Marcello Vieira (Uningá Review, 2023)
The sociology of childhood (hereafter, SI) seeks to reaffirm that children should be perceived as social actors, subjects of rights and co-creators of their culture. It is possible to do this using various languages and narratives, such as in the reality of schools and the streets, or in the fiction of short stories and cinema, as in the work “The 400 Blows” by François Truffaut (1932-1984). The method used was the use of documentary and/ or fiction films as a questioning instrument, and to reflect on the film in the light of IS knowledge, making incursions on the roles of school and family, considered childhood socialising agencies. After the bibliographic survey above, the possibility is allowed that this essay may contribute in an unprecedented way to the discussion of the theme, based on the interconnected reflections between its theory and Truffaut’s filmic elements, particularly the film “The Misunderstood”, from 1959. The constant gaze which sees the children as the future deprives them of any possibility of living the today, of activating their role and effectively connecting with their time. In “The 400 Blows”, one can see Truffaut’s discomfort with school education and the role of the family, denouncing the indifference that the adult world shows towards children. Together with the desire to escape both aesthetic and thematic conventionalism, Truffaut contributes to confronting the desubjectivised view of childhood and as one more support for the critique of the model that is now considered dominant: the adult-centered school model.